SOME QUESTIONS OF BIOMECHANICAL CHARACTER IN WEIGHTLIFTING - Andras S. Szabo (Sport Scientific And Practical Aspects, 2025)
Biomechanics, as a subscience of biophysics is successfully applied for analysis and control of technique of olympic weightlifters. The paper deals with some important questions of biomechanical character in olympic lifting. Special attention is paid to the following topics: efficient and optimum technique, ideal trajectory in snatch and clean, analysis of the barbell+lifter common system, change of category of the lifters from point of view of biomechanics. The paper deals with a new proposition, concerning the analysis and improvement of the technique in olympic weightlifting, based on the complex system. To the new statement the optimum technique means: not the barbell, but the center of the gravity of the common (barbell+lifter) system should be lifted vertically. This statement is valid in case of snatch and also in case of clean and jerk.